Presentation and Treatment of Monozygotic Twins with Congenital Central Hypoventilation Syndrome - Reshma Amin; Andrea Riekstins; Suhail Al-Saleh; Colin Massicotte; Allan L Coates; Ian MacLusky (Canadian Respiratory Journal, 2011)
Congenital central hypoventilation syndrome is a rare genetic disorder characterized by hypoventilation during sleep secondary to a blunted response to hypercapnia and hypoxia. The current case report describes developmentally normal four-year-old monozygotic twin boys who presented in infancy with variable presentations and clinical severity of congenital central hypoventilation syndrome. Both were managed with noninvasive positive pressure ventilation.